Needs of parents and carers of children and young people with mental health difficulties: protocol for a systematic review. Issue 2 (16th February 2023) - Martin, Faith; Dahmash, Dania; Glover, Sarah; Duncan, Charlie; Turner, Andy; Halligan, Sarah L
Abstract : Introduction: Having a child or young person (CYP) with mental health problems can be highly distressing for parents/carers. The impact can include parental/carer depression, anxiety, lost productivity and poor family relationships. Currently, there is no synthesis of this evidence, which is needed to provide clarity around what support parents/carers may need, to meet the needs of family mental health. This review aims to identify the needs of the parents/carers of CYP who are receiving mental health services. Methods and analysis: A systematic review will be conducted to identify potentially relevant studies that provide evidence concerning the needs and impact on parents/carers linked to their CYP having mental health difficulties. CYP mental health conditions included are anxiety disorders, depression, psychoses, oppositional defiant and other externalising disorders, labels of emerging personality disorders, eating disorders and attention deficit (hyperactive) disorders. The following databases were searched on November 2022 with no date restriction applied: Medline; PsycINFO; CINAHL; AMED; EMBASE; Web of Science; Cochrane Library; WHO International Clinical Trials Registry Platform; Social Policy and Practice; Applied Social Sciences Index and Abstracts; and Open Grey. Only studies reported in English will be included. The quality of the included studies will be assessed using Joanna Briggs Institute Critical Appraisal Checklist for qualitative studies and the Newcastle Ottawa Scale for quantitative studies. Qualitative data will be analysed thematically and inductively. Ethics and dissemination: This review was approved by the ethical committee at Coventry University, UK, reference number P139611. The findings from this systematic review will be disseminated across various key stakeholders and published in peer-reviewed journals.